Importance of Pre-pregnancy Counseling in Iran: Results from the High Risk Pregnancy Survey 2012 - Mohammad Eslami; Mahdieh Yazdanpanah; Robabeh Taheripanah; Parnian Andali; Azardokht Rahimi (Kerman University of Medical Sciences, 2013)
Background To identify the prevalence of behavioural (Pre-pregnancy), obstetrical and medical risks of pregnancy in Iranian women. Methods A total of 2993 postpartum women who delivered in 23 randomly selected hospitals of six provinces were enrolled in this nationwide cross-sectional study. A structured questionnaire was completed based on interviewees' self-reports and medical record data, consisting of socio-demographic characteristics, behavioural, obstetrical and medical risks, before and during pregnancy. Results Less than 6.0% had no health insurance and 5.0% had no prenatal visit before labour. Unintended pregnancy was reported by 27.5% of women. Waterpipe and/or cigarette smoking was reported by 7.1% of them and 0.9% abused opiates during pregnancy. Physical abuse by husband in the year before pregnancy occurred in 7.5% of participants. The rate of cesarean section was 50.4%. Preterm birth, low birth weight, and stillbirth were seen in 6.8, 7.7, and 1.2% of deliveries respectively. The most frequent medical risk factors were urinary tract infection (32.5%), anemia (21.6%), and thyroid disease (4.1%). Conclusion More effort should be devoted by health policymakers to the establishment of a preconception counselling (health education and risk assessment) and surveillance system; although obstetrical and medical risks should not be neglected too.